2022
DOI: 10.1159/000526140
|View full text |Cite
|
Sign up to set email alerts
|

Eribulin Treatment for Patients with Metastatic Breast Cancer: The UK Experience – A Multicenter Retrospective Study

Abstract: Purpose: This study examined real-world data from patients who received eribulin for metastatic breast cancer (MBC) collected from 14 hospitals across the UK. Methods: Anonymized data were collected retrospectively from patients with MBC who had received eribulin. The data included hormone-receptor status, histological diagnosis, age, prior chemotherapy, response to eribulin, progression-free survival (PFS), and overall survival (OS). Results: Among 577 patients analyzed, the median age was 56 years and most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 28 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…A recent real-world study from United Kingdom revealed that patients with TNBC had a significantly worse prognosis than HER2(+)/ER(+) patients when treated with eribulin. 30 The expression of hormone receptors is also an independent factor affecting PFS of patients with ABC. Rossi et al showed that HR(+) patients had almost twice as long PFS as HR(−) patients (mPFS: 2.9 vs. 1.4 months, p = 0.0051).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent real-world study from United Kingdom revealed that patients with TNBC had a significantly worse prognosis than HER2(+)/ER(+) patients when treated with eribulin. 30 The expression of hormone receptors is also an independent factor affecting PFS of patients with ABC. Rossi et al showed that HR(+) patients had almost twice as long PFS as HR(−) patients (mPFS: 2.9 vs. 1.4 months, p = 0.0051).…”
Section: Discussionmentioning
confidence: 99%
“…For patients in the late-line use group, who had more metastatic sites and received more previous systemic treatments, the mOS was 14.7 months. 12,13,29 Another multicenter retrospective analysis showed that a significantly better mOS for patients with ≤2 previous chemotherapy lines was compared with those with >2 previous chemotherapy lines (328 vs. 264 days), 30 Oruc et al investigated the factors influencing the outcomes of eribulin treatment in 80 patients with MBC who had experienced 3-10 prior lines of treatment. Their multivariate COX analysis revealed that previous systemic treatment line was an independent prognostic factor affecting PFS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation